Malaria prevalence, transmission potential and efficacy of artemisinin-based combination therapy in the Kenyan Central highlands: a zone previously characterized as malaria-free - Francis T. Kimani; Kelvin K. Thiongó; Maureen A. Otinga; Lewis K. Mbabu; Mary N. Ombati; Stanley K. Kitur; Sarah A. Ochieng’; Lucy N. Wachira; Damaris K. Matoke-Muhia; Luna Kamau (Malaria Journal)
Abstract Background The current study sought to re-evaluate malaria prevalence, susceptibility to artemisinin-based combination therapy (ACT), transmission patterns and the presence of malaria vectors in the Kikuyu area of the Kenyan Central highlands, a non-traditional/low risk malaria transmission zone where there have been anecdotal reports of emerging malaria infections. Methods Sampling of adult mosquitoes was done indoors, while larvae were sampled outdoors in June 2019. The malaria clinical study was an open label non-randomized clinical trial where the efficacy of one ACT drug, was evaluated in two health facilities. Microscopy was used at the facility while nested 18 s rRNA subunit gene PCR amplification and MSP-1 and MSP-2 family alleles genotyping was done in the laboratory. Anti-malarial resistance gene markers Pfk13 and Pfmdr1 were profiled. Results Anopheles funestus mosquitoes were the predominant vectors at 76.35% of all larvae collections (N = 148). Only two non-blood fed, parasites negative adult mosquitoes were collected from houses sampled. Parasitological analysis of the 838 patients screened resulted in 41 positives whose treatment outcome was 100% Adequate Clinical and Parasitological Response (ACPR). From the 35 positive samples genotyped, 29 (82.9%) were polyclonal. The overall mean MOI was 2.8 (95% CI 2.36–3.35). The MOI for msp-1 and msp-2 genes, was 2.02 (95% CI 0.72–2.27) and 2.9 (95% CI 2.22–3.55), and parasite strains range of 1–3 and 1–7, respectively. Polyclonal variation in the two genes was at 76.4% and 70.3%, respectively. The Pfk13 gene revealed no single nucleotide polymorphisms (SNP) associated with suspected artemisinin resistance nor was there any pfmdr1 N86 mutant allele detected. Conclusion The Plasmodium infections positivity rate observed in the study site was very low but significant. A proportion of participants who tested positive did not report recent history of travel. This observation together with the finding of competent known vectors can probably suggest that several of the cases could have been acquired and transmitted locally. The observed genetic diversity and polyclonal variations was on the contrary and suggest that these are imported cases. This however does not rule out a likely changing malaria transmission scenario in this zone, thus the need for further investigations.